Initial Assessment of a Dual-Bioactive Hydrogel Incorporating Phagocytosis-Stimulating and Tissue-Regenerative Proteins for Enhanced Wound Healing - Papassara Changklang; Tan Suwandecha; Somchai Sriwiriyajan; Jongdee Nopparat; Neelam Balekar; Teerapol Srichana (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
Wound healing is a complex process that can be impaired by various factors. Hydrogel is a recommended choice for keeping the skin moist and enhancing wound healing. Hydrogel can contain bioactive compounds to improve wound healing effectiveness further. Phagocytosis activating protein (PAP) and thrombospondin (TSP) can stimulate macrophage and promote cell proliferation. They had the potential to enhance wound healing when incorporated into a hydrogel. This study aims to evaluate the effect of PAP and TSP hydrogel on irritation and wound healing efficacy in a rat model. This experiment is conducted using a full-thickness wounds model in rats. The hydrogel formulations with PAP and/or TSP were applied to the wounds for 21 days. The wound contraction, histology, and TGF-β1 expression were measured. The results showed that low-dose PAP hydrogel had the best wound healing performance among all groups, with high TGF-β1 levels in the early phase and low levels in the late phase. Low-dose TSP hydrogel had similar but weaker effects than low-dose PAP hydrogel. There was no sign of skin irritation for all formulations. Hydrogel containing a low dose of PAP or TSP is a promising formula for further developing new wound dressing materials. It also opens an opportunity to cure some challenging to-treat wounds, such as diabetic and burn wounds.